Trends of injury mortality during the COVID-19 period in Guangdong, China: a population-based retrospective analysis. Issue 6 (2nd June 2021) - Zheng, Xue-Yan; Tang, Si-Li; Ma, Shu-Li; Guan, Wei-Jie; Xu, Xiaojun; Xu, Haofeng; Xu, Ying-Shan; Xu, Yan-Jun; Lin, Li-Feng
Abstract : Objective: We aimed to ascertain the trends of injury mortality during the COVID-19 period in southern China. Methods: We conducted a population-based retrospective analysis to compare the mortality changes of all-cause injury and transport injuries, poisoning, falls, fire/heat/hot substances, drowning, self-harm and interpersonal violence, which were further stratified by sex and age. Comparisons were made between the COVID-19 period (between January 2020 and June 2020) and control period (between January 2019 and June 2019) in Guangdong province. We used the negative binomial models to explore the associations of deaths during the COVID-19 period, according to the different sex and age strata. Results: The all-cause injury mortality in Guangdong province decreased significantly from 28.65 per 100 000 population during the control period to 23.24 per 100 000 population during COVID-19 pandemic period. Similar results were found in specific injury categories. Mortality of self-harm increased by 139.26% in the 10–14 year group during the COVID-19 period as compared with the control period. Although mortality changes in some groups were not statistically significant, some increases were noteworthy during the COVID-19 period (ie, self-harm, transport injury and falls) in the 70–79 year group. The corresponding increase in mortality rate was 16.83%, 3.32% and 4.92%, respectively. Conclusion: The mortality of all-cause injury, transport injury and drowning during the COVID-19 pandemic was consistently decreased. However, the increase in mortality associated with falls, fire/heat/hot substance injury and self-harm in specific age populations warrant the targeted control and prevention measures for the population at risk.